2018
DOI: 10.1103/physrevapplied.9.024037
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Transport in Hydrogen-Terminated Si(001) Nanomembranes

Abstract: Charge carrier transport in thin hydrogen (H)-terminated Si(001) sheets is explored via a fourprobe device fabricated on silicon-on-insulator (SOI) using the bulk host Si as a back-gate. The method enables electrical measurements without a need to contact the sample surface proper. Sheet conductance measurements as a function of back-gate voltage demonstrate the presence of acceptor and donor-like surface states. These states are distributed throughout the gap and can be

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In between these regions, the conductance reaches a minimum value known as Gmin. It is detected that the Gmin value decreases by more than 1 order of magnitude with decreasing membrane thickness from 220 to 70 nm [115]. By comparing the theoretically calculated minimum conductance values of various thickness of Si NMs with the experimentally obtained values, they concluded that NMs thickness governs the coupling strength between the top H-terminated surface and the back gate by modifying the capacitance within the NM.…”
Section: Thickness Dependent Electronic Transport Propertiesmentioning
confidence: 92%
See 2 more Smart Citations
“…In between these regions, the conductance reaches a minimum value known as Gmin. It is detected that the Gmin value decreases by more than 1 order of magnitude with decreasing membrane thickness from 220 to 70 nm [115]. By comparing the theoretically calculated minimum conductance values of various thickness of Si NMs with the experimentally obtained values, they concluded that NMs thickness governs the coupling strength between the top H-terminated surface and the back gate by modifying the capacitance within the NM.…”
Section: Thickness Dependent Electronic Transport Propertiesmentioning
confidence: 92%
“…In a follow-up work, the same research group studied the conductance of various thicknesses of hydrogen (H) terminated Si NMs. The charge carrier transport of H-terminated Si NMs was studied by fabricating a four-probe device on a SOI wafer where the handle Si substrate was used as a back gate [115]. As presented in Fig.…”
Section: Thickness Dependent Electronic Transport Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using moderately doped (p-type and n-type) silicon Huang and Lau [62,63] observed that and dilute HF (<5%) treatment of silicon surface could achieve near-flatband surfaces-although others have observed Fermi-level pinning in HF-treated silicon surfaces [64,65]. Recently, using thin silicon layers, Peng et al [66] found that hydrogen-termination results in surface 'donarlike' states in the 10 11 cm −2 eV −1 range.…”
Section: Hydrogen-terminated Siliconmentioning
confidence: 99%
“…We show the response of the NIH-3T3 fibroblast on three different substrates, namely, bulk Si, 220 nm Si NMs/PDMS, and 20 nm Si NMs/PDMS. The substrates have the same extensively characterized surface chemistry and an effective shear modulus that varies over ∼6 orders of magnitude. Thus, the focus is on the unique mechanics of Si NMs on compliant substrates and how it affects cell behavior.…”
Section: Introductionmentioning
confidence: 99%